In vivo assessment of drug efficacy against Plasmodium falciparum malaria: duration of follow-up. - Stepniewska, K; Taylor, W; Mayxay, M; Price, R; Smithuis, F; Guthmann, J; Barnes, K; Myint, H; Adjuik, M; Olliaro, P; Pukrittayakamee, S; Looareesuwan, S; et al. (2004)
To determine the optimum duration of follow-up for the assessment of drug efficacy against Plasmodium falciparum malaria, 96 trial arms from randomized controlled trials (RCTs) with follow-up of 28 days or longer that were conducted between 1990 and 2003 were analyzed. These trials enrolled 13,772 patients, and participating patients comprised 23% of all patients enrolled in RCTs over the past 40 years; 61 (64%) trial arms were conducted in areas where the rate of malaria transmission was low, and 58 (50%) trial arms were supported by parasite genotyping to distinguish true recrudescences from reinfections. The median overall failure rate reported was 10% (range, 0 to 47%). The widely used day 14 assessment had a sensitivity of between 0 and 37% in identifying treatment failures and had no predictive value. Assessment at day 28 had a sensitivity of 66% overall (28 to 100% in individual trials) but could be used to predict the true failure rate if either parasite genotyping was performed (r(2) = 0.94) or if the entomological inoculation rate was known. In the assessment of drug efficacy against falciparum malaria, 28 days should be the minimum period of follow-up.